2004
DOI: 10.2165/00019053-200422003-00003
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up lipid tests and physician visits are associated with improved adherence to statin therapy

Abstract: Early and frequent follow-up by physicians--especially lipid testing--was associated with improved adherence to lipid-lowering therapy. A randomised prospective study is needed to determine whether this relationship is causal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
58
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 28 publications
7
58
2
1
Order By: Relevance
“…19 Several methods for improving long-term medication adherence have been promoted in the literature, including early physician follow-up, as well as enrollment in cardiac rehabilitation and patient education programs. [19][20][21][22] Of note, patients with MI who undergo outpatient physician follow-up within 1 month after hospital discharge have significantly higher rates of medication use 6 months later. 23 Modest improvements in adherence were noted with the elimination of medication copayments in the MI FREEE trial 14 and in the current surgical subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several methods for improving long-term medication adherence have been promoted in the literature, including early physician follow-up, as well as enrollment in cardiac rehabilitation and patient education programs. [19][20][21][22] Of note, patients with MI who undergo outpatient physician follow-up within 1 month after hospital discharge have significantly higher rates of medication use 6 months later. 23 Modest improvements in adherence were noted with the elimination of medication copayments in the MI FREEE trial 14 and in the current surgical subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…18 Hence, persons who have been newly prescribed medications comprise an interesting subgroup when pharmaceutical care programs are implemented. Most studies aimed at improving adherence among users of statins were hospital pharmacy-based, 7-10,14, 16 sometimes with complex interventions 10,14, 17 and mostly not focusing solely on patients initiating statin treatment.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9] In 4 of these studies, 4,7-9 a positive relation was observed. For example, a high level of continuity of care was associated with higher persistence with statins 8 and higher compliance with treatment with orally administered antidiabetics, 7 statins 9 and drugs used in heart failure. 4 However, 5 of these studies 4,[6][7][8][9] were limited by the fact that their design was cross-sectional.…”
mentioning
confidence: 76%
“…For example, a high level of continuity of care was associated with higher persistence with statins 8 and higher compliance with treatment with orally administered antidiabetics, 7 statins 9 and drugs used in heart failure. 4 However, 5 of these studies 4,[6][7][8][9] were limited by the fact that their design was cross-sectional. Therefore, the temporal relation between continuity of care and medication adherence could not be established.…”
mentioning
confidence: 99%